If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6(7 + 2m) + -8m = 0 (7 * -6 + 2m * -6) + -8m = 0 (-42 + -12m) + -8m = 0 Combine like terms: -12m + -8m = -20m -42 + -20m = 0 Solving -42 + -20m = 0 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '42' to each side of the equation. -42 + 42 + -20m = 0 + 42 Combine like terms: -42 + 42 = 0 0 + -20m = 0 + 42 -20m = 0 + 42 Combine like terms: 0 + 42 = 42 -20m = 42 Divide each side by '-20'. m = -2.1 Simplifying m = -2.1
| 3x/8=19 | | 2x+5=x+5+2x-70 | | -8r+27=-4(-7-r)-1 | | 3(w-1)=-12 | | 4+16x=7x+40 | | ln(9x+80)=ln(8x+71) | | 4(-7n-5)=12+4n | | 2x^2+8x-x-4=18 | | 4x+20=2x+25+x+20 | | 3x+4y=6.8 | | X-512=487 | | 40-6x=-90x+40 | | -53=n+7 | | X^2+2xy=-8 | | 9(4-6)+55= | | -15.00-2.00x=25.00 | | f(x)=5x^2+10x+3 | | -15.00-12.00x=25.00 | | 5.75=3/4x | | -7(r-9)= | | 5(2x+3)=4x-9 | | 6r+5(4r-12)= | | 7+7x=2x+32 | | 85=m-4 | | 43+10n=24n-27 | | (x-4y)dx+(x+2y)dy=0 | | 4.8/2 | | 2.5/465 | | 7(5n+9)+n= | | h(t)=27 | | Log(8)+log(-5x)=1 | | -5m+45=27-7m |